MR findings in seven patients with organic mercury poisoning (Minamata disease). - Korogi, Y; Takahashi, M; Shinzato, J; Okajima, T (American Journal of Neuroradiology, 1994)
PURPOSE To study the long-term MR findings in seven patients with Minamata disease. METHODS All patients examined were affected after eating daily considerable amounts of the methylmercury-contaminated seafoods from 1955 through 1958 and showed typical neurologic findings. T1- and T2-weighted images were obtained in axial, coronal, and sagittal sections. RESULTS The visual cortex, the cerebellar vermis and hemispheres, and the postcentral cortex were significantly atrophic. The visual cortex was slightly hypointense on T1-weighted images and hyperintense on T2-weighted images, probably representing the pathologic changes of status spongiosus. CONCLUSION MR demonstrated the lesions, located in the calcarine area, cerebellum, and postcentral gyri, which are probably related to three of the characteristic manifestations of this disease: the constriction of the visual fields, ataxia, and sensory disturbance, respectively.